Globalization and Civil Society in East Asian Space - Chiharu Takenaka; Khatharya Um (Politics in Asia, 2023)
This book critically examines the impact of globalization, changing power dynamics, migration, and evolving rights regimes on regional order, discourse of national governance, state and society relations, and the development of civil society in East Asia. Providing a textured, critical reading of East Asia as an economically, socially, and politically dynamic region, this book also presents the region as one shaped simultaneously by progressive as well as regressive pulls. Attentive to prevailing issues as well as to states’ and civil societies’ responses to them, it focuses on changing societies and politics in East Asia, particularly on shifting notions of citizenship, nationhood, and peoplehood. The contributions feature new and timely conclusions drawn from multidisciplinary fields including law, public policy, sociology, Asian studies, gender, sexuality, and ethnic studies and include direct testimonies from citizens of East and Southeast Asia. Globalization and Civil Society in East Asian Space will appeal to students and scholars of sociology, political science, and Asian studies more broadly.